BOʻLAJAK FIZIKA O'QITUVCHILARINING METODIK TAYYORGARLIGINI TAKOMILLASHTIRISHNING DOLZARB MUAMMOLARI - Bazarbaev, Z.B. (SCIENCE and SOCIETY, 2022)
The systematic organization of the educational process in pedagogical universities plays a significant role in improving the methodological competence of future physics teachers, training highly qualified, highly competitive personnel in the labor market. This article presents topical issues of high-quality organization of the educational process to achieve high efficiency in the training of qualified personnel.
Keywords: future physics teachers; innovation; competence; educational process; knowledge; skills and abilities